Establishment and characterization of usm-bc-1 cell line derived from human urinary bladder cancer - Tajuddin, Wan Nur Baitty Wan Mohd (2013)
Transitional cell carcinoma of the urinary bladder is one of the common diseases that causes morbidity and mortality worldwide. In Malaysia, it lines in the 10 most frequent cancer occurred among males. Since most of the current urinary bladder cancer cell lines were established from populations in western countries while significant genotypic variations have been reported among various populations, this project aimed at establishing the first cell line for providing an ideal cancer cell model for population in Malaysia and countries nearby acquires significance. The urinary bladder cancer cells were isolated from bladder cancer tissues obtained from a Malay patient and the cells obtained were cultured continuously over 30 passages ( > 2 years). The cell line was characterized by observing its morphology, growth characteristics, presence of cytokeratin 7 and desmin markers, expression of Ki-67, vascular endothelial growth factor (VEGF) as well as p21 proteins. Chromosome analysis also was performed to further characterize the cell line designated as USM-BC-1. The authenticity of the obtained cells was investigated using Short Tandem Repeat (STR) analysis and contamination by mycoplasma species was ascertained. Results revealed that the USM-BC-1 cell line was composed of predominantly elongated spindle shape cells with clearly defined margins and no mycoplasma was found contaminating the established cell line. The population of monolayer cells doubled at about 44.6 hours and exhibited good viability when grown from cryopreserved stocks. Positive staining for cytokeratin 7 confirmed the identity of the urothelial cells while the negative staining for desmin indicated the absence of fibroblast. Ki-67 (345 kDa) was highly expressed in the USM-BC-1 cell line indicating high proliferation rate of USM-BC-1 cell. Meanwhile, both VEGF and p21 expressions remained low indicating the possible role of other angiostimulatory proteins and the USM-BC-1 cell line possess neoplastic behavior, respectively. Chromosomal study proved the occurance of genetic instability when the cell line exhibited unstable chromosome numbers ranged from 44-57 with a modal number of 44, abnormal chromosomes structure and no Y chromosome observed in 80% of the metaphase cells. The high similarity (96 %) in the sequence of the STR observed between the donor and the newly established cell line further confirmed its authenticity. Hence, this newly established cell line (USM-BC-1) that has been well characterized may prove useful in cancer research for developing future diagnostic and therapeutic targets, taking into consideration the genotypic variations among Asian population.